PENGARUH KOORDINASI TERHADAP EFEKTIVITAS KERJA PEGAWAI BADAN PENDAPATAN DAERAH KABUPATEN KUTAI TIMUR - Rusnawati rusnawati (ADMINISTRASI PUBLIK, 2020)
Rusnawanti, a thesis with the title of coordination influence on the effectiveness of employee work on the local revenue body of East Kutai regency. This research aims to determine and describe the influence of coordination on the effectiveness of employees ' work on the local Revenue Board of Kutai Timur District. Analysis of data used to test the relationship or influence coordination to the effectiveness of work, using analytical instruments coefficient correlation product moment.The population of this study was 95 PNS, which became a sample of 33 employees. Sampling techniques used are Sampling Purposive, civil servants who occupy structural offices and perform coordination functions both internally and externally.Based on the calculation of the calculated  Rs price of Rhit = 0.412, the result is greater when compared to the price-critical price table of the correlation coefficient for n – 2 = 31 (33 – 2 = 31).  This means that there is a significant relationship and influence between coordination variables and working effectiveness variables.Product Moment (Pearson) to n = 33 at a signification rate of 5%, i.e. 0.279. Or can be said also that Rhit = 0.412 > Rtab = 0.279. This means that there is a positive relationship between coordination variables and employee work effectiveness.Based on the result of test-t calculation is 4.623.  This means it can also be said that Thit = 4.623, this result when compared to the value on the table price-critical price of T-student is apparently greater, i.e. Thit = 4.623 > Ttab = 1.701 at a signification rate of 0.05 for n – 2 = 31 (33 – 2 = 31).  This means that there is a significant relationship and influence between coordination variables and working effectiveness variables.Based on the calculation of coefficiencies determinant, the value of R Square or R2 is 35%. Based on such data, it can be noted that the magnitude of coordination influence on the effectiveness of staff work at the District Revenue Board (Bapenda) East Kutai District is 35%, and 65% is influenced by other factors that are not measured in this study.  The meaning is that as many as 35% of employees ' work effectiveness is influenced by the dominant factors of direction/briefing, the implementation of the organization meetings and direct inductions or direct supervision of leaders, and the remainder of the 65% service effectiveness is influenced by other factors measured in this research.The results of the research that coordination function can not walk by itself, highly dependent on aspects or other management functions such as organizing, actuating and controlling and others. The implementation of a number of admnistracy and management functions depends on the leader in implementing the leadership style to the employees.